New occurrences of Lower Cretaceous ammonites in the western part of the Silesian Unit (Barremian - early Aptian, Outer Western Carpathians, Czech Republic) - Vasicek,Z.; Skupien,P.; Sulgan,F. (Journal of the Czech Geological Society, 2004)
During the recent field research of the Silesian Unit, we have succeeded in obtaining a rather small collection of interesting and stratigraphically important Lower Cretaceous ammonites from the Hradiste Formation. Taxonomically, eight species have been processed, two of them being new species: Anahamulina uhligi and A. pindulensis. The ammonites described and their accompanying associations show the age from the higher early Barremian to the early Aptian.
Keywords: Silesian Unit; Lower Cretaceous; Barremian; lowermost Aptian; ammonites